Clinical characteristics and therapeutic strategy for patients with spontaneous isolated abdominal aortic dissection - Zhao, Zhengde; Liu, Jiawei; Liu, Yunchong; Huang, Kan; Wang, Mian; Wu, Ridong; Hu, Zuojun; Yao, Chen; Li, Zilun; Chang, Guangqi (Frontiers in Cardiovascular Medicine, 2023)
Objective: Spontaneous isolated abdominal aortic dissection (SIAAD) is a rare aortic emergency and not yet fully understood. This study aims to report the characteristics and treatments of 31 patients with SIAAD in the past 12 years.Methods: A total of 31 consecutive patients with SIAAD between 2010 and 2022 were included. The clinical manifestations, treatment strategies, and outcomes were reviewed.Following the SVS/STS reporting standard, we compared the clinical characteristics with different locations of primary entry, or different numbers of dissected zones. Furthermore, we compared the effects of surgical and conservative therapies on the outcome during the follow-up.Results: Among the 31 patients with SIAAD, 16 (51.6%) were in the acute phase on admission. The primary entry of SIAAD was mainly located in Zone 9 (67.7%). Most patient presented with dissection involving 1 or 2 aortic zones (61.3%). In addition, 35.5% and 64.5% of SIAADs involved the visceral and iliac arteries, respectively. Compared with asymptomatic SIAADs, the symptomatic ones had longer dissection lengths (P = 0.008) and tended to involve iliac artery more frequently (P = 0.098). There were differences in the number of dissected aortic zones (P = 0.005) among patients with primary entry located in Zone 5 (Supraceliac aorta), Zone 6-8 (Paravisceral aorta) and Zone 9 (Infrarenal aorta).The involvement of visceral artery (P = 0.039) and iliac artery (P = 0.006) was significantly different between the subgroups of SIAAD involving one, two, and three or more aortic zones. The cumulative incidence of adverse false lumen progression events was significantly lower (P = 0.000) and the rate of false lumen thrombogenesis or disappearance was higher in patients receiving surgery (P = 0.001). The cumulative allcause mortality was 9.7% at 1-year, and 19.7% at 5-year, with no significant difference between surgical and conservative therapies.Conclusions: Clinical features of SIAAD vary depending on the location of the primary entry and the number of dissected aortic zones. Although surgery was not associated with a lower all-cause mortality compared with conservative therapy, it associated with a lower incidence of adverse false lumen progression and a higher rate of aortic remodeling.